2021
DOI: 10.1016/j.arth.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Knee Kinematics: How Important Are the Roles of Femoral Geometry and the Cruciate Ligaments?

Abstract: Background: While posterior cruciate-retaining (PCR) implants are a more common total knee arthroplasty (TKA) design, newer bicruciate-retaining (BCR) TKAs are now being considered as an option for many patients, especially those that are younger. While PCR TKAs remove the ACL, the BCR TKA designs keep both cruciate ligaments intact, as it is believed that the resection of the ACL greatly affects the overall kinematic patterns of TKA designs. The objectives of this study are to assess the in vivo kinematics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Multiple authors have shown that the motion of the normal knee joint depends on the interaction between the shape of the articular surfaces and the ligaments crossing the knee joint [ 3 , 39 ]. In the normal knee, the femoral condyles undergo a combination of rolling, sliding, and rotation on the tibial plateau during flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors have shown that the motion of the normal knee joint depends on the interaction between the shape of the articular surfaces and the ligaments crossing the knee joint [ 3 , 39 ]. In the normal knee, the femoral condyles undergo a combination of rolling, sliding, and rotation on the tibial plateau during flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In TKA, sacrificing the ACL reportedly achieved inferior clinical outcomes 21 . Moreover, compared to posterior cruciate-retaining (PCR)-TKA, BCR-TKA achieved more normal-like kinematics 22 . Finally, it has been reported that normal-like kinematics promote favorable clinical outcomes 23 .…”
Section: Discussionmentioning
confidence: 99%
“…None of the other papers reporting outcomes of the JII-BCS compared the JII-BCS to the Genesis II, none used a randomised design and none used methodology or outcomes that could be compared with the methodology used in this trial. [42][43][44][45][46] However, on the basis of the available literature, we measured outcomes that would be expected to be difference on the basis of the available literature, walking velocity, step-length symmetry (resulting from longer stride length), knee ROM and peak knee angular velocity. Within our trial, we found differences in some biomechanical measures of motor impairment but not for others; patient-reported outcomes; and, walking and balance function.…”
Section: Open Accessmentioning
confidence: 99%